2021
DOI: 10.1097/md.0000000000027180
|View full text |Cite
|
Sign up to set email alerts
|

An association between electronic nicotine delivery systems use and a history of stroke using the 2016 behavioral risk factor surveillance system

Abstract: Electronic nicotine delivery systems (ENDS) are growing in use and many of the health implications with these devices remain unknown. This study aims to assess, using a survey representative of the USA general population, if an association exists between a history of ENDS use and a history of stroke. This cross-sectional study was a secondary data analysis using the 2016 behavioral risk factor surveillance system survey. The main exposure variable of the study was a self-reported history of ENDS use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…In our study, the use of marijuana was associated with higher odds of stroke. Similar to cocaine and marijuana use, our study also showed higher odds of developing a stroke with e-cigarette use and heroin use, consistent with existing evidence [31,32].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the use of marijuana was associated with higher odds of stroke. Similar to cocaine and marijuana use, our study also showed higher odds of developing a stroke with e-cigarette use and heroin use, consistent with existing evidence [31,32].…”
Section: Discussionsupporting
confidence: 91%
“…36 In this study, FMD was significantly lower in both e-cigarette users and cigarette smokers relative to nonusers by >5%, suggesting that the effect is clinically significant. Conclusions from studies of the association of chronic e-cig use and CVD in humans have been mixed, 37–48 our study is important in showing a clear increase in early indicators of cardiovascular risk in otherwise healthy vapers.…”
Section: Discussionmentioning
confidence: 79%
“…There are other unfavorable health effects of electronic cigarette use indicated by observational human studies, including association with stroke [ 14 ] and myocardial infarction [ 20 ]. Another adverse outcome from animals studies was observed by one study [ 21 ] in which electronic cigarette vapor caused the development of cardiac hypertrophy.…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 shows the summary of the quality assessment. Two studies were judged as good [ 15 , 16 ], three studies were fair [ 14 , 17 , 19 ], while two studies were deemed as poor [ 18 , 20 ].…”
Section: Resultsmentioning
confidence: 99%